(untitled) (The International Journal for Scientific Research, 2026)
The present study aimed to investigate the relationship between depression and meaning in life among widowed women in northern Syria, as well as to examine differences in meaning in life and depression between widowed and non-widowed women. The study included a sample of 102 widowed and non-widowed women and adopted a descriptive research design. To achieve the study’s objectives, Haroun Al-Rashidi’s Meaning in Life Scale (1996) and the Beck Depression Inventory were employed. The findings revealed a negative correlation between meaning in life and depression among widowed women. Furthermore, the sample demonstrated a moderate level of meaning in life and a below-average level of depression. The results also indicated that there were no statistically significant differences in meaning in life and depression between widowed and non-widowed women.